Angiostrongylus cantonensis and Rat Lungworm Disease in Brazil - Thiengo, Silvana Carvalho (University Clinical, Education & Research Associate (UCERA), 2013)
The metastrongyloid nematode genus Angiostrongylus includes 18 species, two of which are relevant from a medical standpoint, Angiostrongylus costaricensis and Angiostrongylus cantonensis. The first was described from Costa Rica in 1971 and causes abdominal angiostrongyliasis in the Americas, including in Brazil. Angiostrongylus cantonensis, first described in 1935 from Canton, China, is the causative agent of eosinophilic meningitis. The natural definitive hosts are rodents, and molluscs are the intermediate hosts. Paratenic or carrier hosts include crabs, freshwater shrimp, amphibians, flatworms, and fish. Humans become infected accidentally by ingestion of intermediate or paratenic hosts and the parasite does not complete the life cycle as it does in rats. Worms in the brain cause eosinophilic meningitis. This zoonosis, widespread in Southeast Asia and the Pacific islands, has now been reported from other regions. In the Americas there are records from the United States, Cuba, Jamaica, Brazil, Ecuador, and Haiti. In Brazil seven human cases have been reported since 2007 from the southeastern and northeastern regions. Epidemiological studies found infected specimens of Rattus norvegicus and Rattus rattus as well as many species of molluscs, including the giant African land snail, Achatina fulica, from various regions of Brazil. The spread of angiostrongyliasis is currently a matter of concern in Brazil.